Unveiling the Critical Role of Ion Coordination Configuration of Ether Electrolytes for High Voltage Lithium Metal Batteries - Chen, Shunqiang; Fan, JiaJia; Cui, Zhuangzhuang; Tan, Lijiang; Ruan, Digen; Zhao, Xin; Jiang, Jinyu; Jiao, Shuhong; Ren, Xiaodi (Angewandte Chemie International Edition, 2023)
Albeit ethers are favorable electrolyte solvents for lithium (Li) metal anode, their inferior oxidation stability (<4.0 V vs. Li/Li+) is problematic for high‐voltage cathodes. Studies of ether electrolytes have been focusing on the archetype glyme structure with ethylene oxide moieties. Herein, we unveil the crucial effect of ion coordination configuration on oxidation stability by varying the ether backbone structure. The designed 1,3‐dimethoxypropane (DMP, C3) forms a unique six‐membered chelating complex with Li+, whose stronger solvating ability suppresses oxidation side reactions. In addition, the favored hydrogen transfer reaction between C3 and anion induces a dramatic enrichment of LiF (a total atomic ratio of 76.7 %) on the cathode surface. As a result, the C3‐based electrolyte enables greatly improved cycling of nickel‐rich cathodes under 4.7 V. This study offers fundamental insights into rational electrolyte design for developing high‐energy‐density batteries. A new ether solvent (1,3‐dimethoxypropane, DMP) is used for the configuration of the electrochemical behavior of electrolytes in lithium metal batteries. The six‐membered Li+‐chelating ring greatly improves the oxidation stability of the ether‐based electrolyte compared to the conventional five‐membered chelate ring. The cathode‐electrolyte interphase enriched in LiF effectively protects the nickel‐rich cathode from corrosion by electrolyte side reactions.